Situation analysis on the regulation of nanomedicines in Southern Africa - Mudyiwenyama, Linda G.; Khoza, Star; Dube, Admire (Frontiers in Medicine, 2023)
Medical products incorporating nanoparticle drug delivery systems (nanomedicines) are therapeutic or imaging agents, which comprise a delivery system within the nanometer size range (1 – 1000 nm). As medical products, nanomedicines meet definitions of medicines according to various national legislations for regulation of medicines. However, for the regulation of nanomedicines, additional assessments including toxicological issues have to be considered. These complexities require extra regulatory effort. In the resource-limited context of low- and middle-income countries, many National Medicines Regulatory Authorities (NMRAs) lack resources and capacities to effectively assure the quality of medicinal products in their countries. With emerging trends in innovative technologies, including nanotechnology, this burden is worsened. The need to overcome regulatory challenges drove the formation of a work sharing initiative in the Southern African Development Community (SADC), ZaZiBoNA in 2013. Regulatory agencies participating in this initiative cooperate in the assessment of applications for registration of medicines.